The global curse of the Federal Reserve : manifesto for a second monetarist revolution - Brown, Brendan, 1951- (New York, NY : Palgrave Macmillan, 2011)
The book reveals how the Global Credit Bubble and Bust of 2003-10 stemmed from giant monetary disequilibrium created by the Federal Reserve. Almost continually that institution has pursued flawed monetary practice and principle which has mutated into Bernanke-ism. The book dissects this and shows how it threatens the return of economic prosperity.
A 100-year monetary disorder -- Phobia of deflation menaces prosperity -- Manifesto for a second monetarist revolution -- Currency war machine -- The revolt against Bernanke-ism.
Includes bibliographical references (p. 178-181) and index.
oif 08/09/14
Loan
Keywords: Money -- United States -- History; Currency question -- United States -- History; Monetary policy -- United States